Effects of Resources Exploitation on Water Quality: case studies in Salt Water Intrusion and Acid Mine Drainage - Kralj, Martina <1981> (Alma Mater Studiorum - Università di Bologna, 2012)
Throughout the world, pressures on water resources are increasing, mainly as a result of human activity. Because of their accessibility, groundwater and surface water are the most used reservoirs. The evaluation of the water quality requires the identification of the interconnections among the water reservoirs, natural landscape features, human activities and aquatic health. This study focuses on the estimation of the water pollution linked to two different environmental issues: salt water intrusion and acid mine drainage related to the exploitation of natural resources. Effects of salt water intrusion occurring in the shallow aquifer north of Ravenna (Italy) was analysed through the study of ion- exchange occurring in the area and its variance throughout the year, applying a depth-specific sampling method. In the study area were identified ion exchange, calcite and dolomite precipitation, and gypsum dissolution and sulphate reduction as the main processes controlling the groundwater composition. High concentrations of arsenic detected only at specific depth indicate its connexion with the organic matter. Acid mine drainage effects related to the tin extraction in the Bolivian Altiplano was studied, on water and sediment matrix. Water contamination results strictly dependent on the seasonal variation, on pH and redox conditions. During the dry season the strong evaporation and scarce water flow lead to low pH values, high concentrations of heavy metals in surface waters and precipitation of secondary minerals along the river, which could be released in oxidizing conditions as demonstrated through the sequential extraction analysis. The increase of the water flow during the wet season lead to an increase of pH values and a decrease in heavy metal concentrations, due to dilution effect and, as e.g. for the iron, to precipitation.